A comparative evaluation of phenolic hydroxyl content of oil palm - Varman, M.; Saka, S. (2015)
Free phenolic hydroxyl content was determined in various parts of oil palm (Elaeis guineensis) such as trunk, frond, mesocarp, shell, empty fruit bunch and comparatively evaluated by aminolysis and periodate oxidation methods. This determination will elucidate the reactivity of lignin in oil palm and provide information for its future efficient utilisation. The results showed that aminolysis method consistently yielded higher values for phenolic hydroxyl content than the periodate oxidation method. More phenolic hydroxyl content was observed in the trunk, mesocarp and frond than in the shell and empty fruit bunch. As a comparison, phenolic hydroxyl content was also evaluated for hardwood, Japanese beech (Fagus crenata) and softwood, Japanese cedar (Cryptomeria japonica) for their sapwood portions. These samples have been selected because of their anatomical differences whereby, under botanical terms, oil palm is classified as one of monocotyledonous angiosperms, Japanese beech is classified as one of dicotyledonous angiosperms and Japanese cedar is classified as gymnosperms. Due to the abrupt increase in the formation of 1-acetylpyrrolidine in the aminolysis method, small discrepancy did exist between aminolysis and periodate oxidation methods, but the trend on the phenolic hydroxyl content was similar.